Increasing Rumen Microbial Protein Synthesis with Additional Dietary Substrate of Saccharomyces cerevisiae and Soybean Oil - Suryapratama, W; Suhartati, FM (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Absract. A study with the purpose to increase microbial protein synthesis was carried out using in vitro experiment with 2x2 factorial. Completely Randomized Design were used in this study. The first factor was with or without substrate of Saccharomyces cerevisiae. The second factor was the addition of 2 levels of soybean oil, 0% and 3%. There were 4 treatments, each treatment was replicated 5 times so that there were 20 experimental units. The materials of this research were Napier grass, concentrates and substrate of Saccharomyces cerevisiae, consisted of a mixture of 30% rice bran, 20% tapioca by-product, 20% coconut meal, 20% corn, 9% pollard, 1% mineral, and soybean oil. The rumen fluid as a source of rumen inoculum was taken immediately after a cattle was slaughtered in the slaughterhouse. The variables measured were N-NH3 concentration and the product of rumen microbial protein synthesis. Data were analyzed using analysis of variance, followed by a test of Honestly Significant Differences (HSD). The conclusion was that the use of substrate of Saccharomyces cerevisiae increased rumen microbial protein synthesis as much as 9.42% and the use of 3% of soybean oil increased rumen microbial protein synthesis as much as 18.64%. Keywords: rumen microbe, Saccharomyces cerevisiae, soybean oil Abstrak. Sebuah studi dengan tujuan untuk meningkatkan sintesis protein mikroba dilakukan dengan menggunakan percobaan in vitro dengan pola faktorial 2x2. Rancangan Acak Lengkap digunakan dalam penelitian. Faktor pertama adalah dengan atau tanpa substrat Saccharomyces cerevisiae. Faktor kedua adalah penambahan 2 level minyak kedelai, 0 % dan 3 %. Penelitian melibatkan 4 perlakuan dan setiap perlakuan diulang 5 kali sehingga ada 20 unit percobaan. Materi penelitian ini adalah rumput gajah, konsentrat dan substrat Saccharomyces cerevisiae, terdiri dari campuran 30 % dedak padi, 20 % produk samping tapioka, 20 % bungkil kelapa, 20% jagung, 9% pollard, 1% mineral, dan minyak kedelai. Cairan rumen sebagai sumber inokulum rumen diambil sesaat setelah ternak disembelih di rumah potong. Variabel yang diukur adalah konsentrasi N-NH3 dan produk dari sintesis protein mikroba. Data dianalisis dengan menggunakan analisis variansi, dilanjutkan dengan uji Beda Nyata Jujur (HSD). Kesimpulannya adalah bahwa penggunaan substrat Saccharomyces cerevisiae meningkatkan sintesis protein mikroba sebesar 9,42% dan penggunaan 3% minyak kedelai meningkatkan sintesis protein mikroba rumen sebesar 18,64%. Kata kunci : mikroba rumen, Saccharomyces cerevisiae, minyak kedelai W Suryapratama and FM Suhartati/Animal Production 14(3):155-159, September 2012